2000
DOI: 10.1530/eje.0.1420445
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-term, non-suppressive levothyroxine treatment on quantitative ultrasonometry of bone in women

Abstract: Objective: To evaluate the impact of long-term, non-suppressive levothyroxine (L-T 4 ) treatment on quantitative ultrasonometry in women.Design: This was a case-control study. Subjects and methods: Altogether 667 women (mean age Ϯ S.D., 49.5 Ϯ 13.1 years) were studied. Of these, 156 (23%) had non-toxic goitre or hypothyroidism and had been taking L-T 4 (75-100 mg/day) for at least 5 years (mean Ϯ S.D., 12.5 Ϯ 7.5 years); the remaining 511 (77%) women were not receiving L-T 4 . All women had completed a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
1
15
0
3
Order By: Relevance
“…The longest trial where patients were followed for one year after the initiation of therapy supports the finding in the current study. Many other studies have shown significant bone loss after a minimum of 7.5 years of LT4 replacement therapy as evidenced by a significant attenuation in speed of sound and stiffness index of the ultrasound measurements at the heel region 34,35. The technique used to measure BMD in these studies was similar to our study as were the findings.…”
Section: Discussionsupporting
confidence: 88%
“…The longest trial where patients were followed for one year after the initiation of therapy supports the finding in the current study. Many other studies have shown significant bone loss after a minimum of 7.5 years of LT4 replacement therapy as evidenced by a significant attenuation in speed of sound and stiffness index of the ultrasound measurements at the heel region 34,35. The technique used to measure BMD in these studies was similar to our study as were the findings.…”
Section: Discussionsupporting
confidence: 88%
“…The lack of ultrasensitive thyroid-stimulating hormone (TSH) assay and densitometers with adequate precision and the heterogeneity of study protocols and analyzed series could explain these discordant results [1,2,3,4,5,6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Among other methods also QUS was successfully used in order to assess bone side effects [85][86][87][88][89]. QUS values were decreased in patients with Cushing syndrome [85].…”
Section: -Endocrinologymentioning
confidence: 99%
“…QUS values were decreased in patients with Cushing syndrome [85]. QUS was used to evaluate bone status in girls treated by growth hormone [89], and in women on long-term therapy using non-supressive doses of thyroid hormones QUS values at calcaneus were decreased in comparison to controls [88]. The latter observation seems of clinical importance because the number of females taking thyroid hormones is high and bone-side effects in this group of patients usually is not adequately estimated.…”
Section: -Endocrinologymentioning
confidence: 99%